What configurational conditions promote tourism eco-transformation? a fuzzy-set qualitative comparative analysis based on the TOE framework - Wang, Chao; Zheng, Qiujin; Zeng, Haimei; Wu, Yizhen; Wei, Chenwen (Frontiers in Environmental Science, 2022)
Tourism eco-transformation can provide a long-lasting competitive advantage. However, successful transformation is a challenge for both academia and industry. The literature has focused on the net effect of a single factor. Still, we build on the TOE framework and propose that tourism eco-transformation does not depend on a single condition but the configurational effect of organization, environment and technology. Using an analysis of Chinese provinces, we identified six conditions influencing eco-transformation. The results show that (1) the tourism eco-transformation in China from 2016 to 2019 "declines first and then rises," indicating a "U" shape. (2) High-level transformations can be classified into four configurational types: technology-pulling organization, proactive organization, environmental stress organization, and comprehensive organization. Not-high level transformations can be categorized as comprehensive absence and respectable; (3) There are three critical conditions for tourism external connections, environmental regulation, and tourism ecology promotion. In contrast, digital information level, technology innovation capability, and tourism resource endowment must be determined based on the specific situation; These findings enrich the literature on tourism eco-transformation and provide insights for tourism authorities and enterprises.